2020
DOI: 10.1111/1747-0080.12645
|View full text |Cite
|
Sign up to set email alerts
|

Choosing and following a very low calorie diet program in Australia: A quasi‐mixed methods study to understand experiences, barriers, and facilitators in a self‐initiated environment

Abstract: Aim In Australian adults, this study seeks to describe the experiences and factors associated with the perceived outcomes of using a very low calorie diet (VLCD) program for ≥4 weeks. Methods A mixed method study using the method perspective was conducted to analyse individual semi‐structured interviews conducted via videoconference and cross‐sectional survey data. Australians 18 to 65 years were eligible if they were currently consuming at least one VLCD product daily for ≥4 weeks or had ceased consumption wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…It is notable that many of our participants were still regularly using meal replacement products in the 6 months after the programme had ended, some of whom were still replacing two meals per day and following principles of the ketogenic restriction phase of the diet. This reflects the findings of a recent mixed-methods study that explored experiences of Australians who followed a VLCD 51. It found that people felt dependent on the VLCD in the long-term as they were afraid of regaining the weight they had lost, and of losing the benefits that had been achieved.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It is notable that many of our participants were still regularly using meal replacement products in the 6 months after the programme had ended, some of whom were still replacing two meals per day and following principles of the ketogenic restriction phase of the diet. This reflects the findings of a recent mixed-methods study that explored experiences of Australians who followed a VLCD 51. It found that people felt dependent on the VLCD in the long-term as they were afraid of regaining the weight they had lost, and of losing the benefits that had been achieved.…”
Section: Discussionsupporting
confidence: 72%
“…This reflects the findings of a recent mixed-methods study that explored experiences of Australians who followed a VLCD. 51 It found that people felt dependent on the VLCD in the long-term as they were afraid of regaining the weight they had lost, and of losing the benefits that had been achieved. This is a potentially undesirable finding given that the ketogenic restriction phase of the diet is not usually advocated for long-term use 52 due to the potential negative effects on electrolyte balance, hypotension and gallstones.…”
Section: Discussionmentioning
confidence: 99%
“…Despite no statistical improvement, overall QoL and all domains of QoL in the ESG group were clinically meaningful and further research with large sample sizes is needed to confirm the finding. Although causation cannot be inferred, the moderate correlations between QoL and %EWL suggests there may be many factors influencing QoL improvements following bariatric procedures, a finding which aligns with lifestyle obesity treatments [ 57 ]. In depth qualitative research has revealed that weight loss following bariatric surgery has led to complex changes in self-perception as well as impacting upon relationships, which are closely aligned with mental health and quality of life [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 Scale scores ranged from 0 to 21, with larger scores indicating adverse mental health scores; depression: normal (0-4), mild (5-6), moderate (7-10), severe (11)(12)(13), extremely severe (14þ): anxiety; normal (0-3), mild (4-5), moderate (6-7), severe (8-9), extremely severe (10þ); stress: normal (0-7), mild (8-9), moderate (10)(11)(12), severe (13)(14)(15)(16), extremely severe (17þ).…”
Section: Resultsmentioning
confidence: 99%
“…A previous mixed methods study identified several individuals (e.g., mental health), program (e.g., program structure/levels), and environmental (e.g., online or HCP support) barriers and facilitators which may influence success and adherence to a VLCD program in Australian adults (n = 31). 13 Therefore, this study aimed to determine the demographic, eating, self-efficacy and program engagement characteristics of different types of VLCD users in Australia (regular vs. intermittent users) and the associations between these user characteristics and self-perceived program success on weight loss, QOL, mental health and physical health. It was hypothesized that user type (regular vs. intermittent use) would be related to different demographic, eating, self-efficacy, and engagement factors, which may relate to program success.…”
Section: Introductionmentioning
confidence: 99%